Amorphous NiB@IrOx nanozymes trigger efficient apoptosis-ferroptosis hybrid therapy. (1st January 2023) - Wang, Qin; Shaik, Firdoz; Lu, Xiuxin; Zhang, Wenhao; Wu, Yafei; Qian, Haisheng; Zhang, Weiqing
Abstract: The apoptosis-ferroptosis hybrid therapy opens up a new avenue for tumor eradication. Constructing efficient self-cascade platform is highly desired to enhance its therapeutic effect. Herein, we report on the synthesis of novel nanozyme consist of amorphous NiB alloy completely coated with an ultrathin layer of IrOx shell (A-NiB@C-IrOx ). These core-shell nanoparticles exhibited peroxidase (POD)-, catalase (CAT)- and glutathione oxidase (GSH-OXD)-like properties for inducing self-cascade catalysis. Specifically, the amorphous IrOx shell with abundant active sites can effectively convert intratumor hydrogen peroxide (H2 O2 ) to cytotoxic reactive oxygen species (ROS) and oxygen (O2 ). In presence of O2, amorphous NiB core and ultrathin IrOx shell collectively catalyze the oxidation of GSH to generate H2 O2, which is subsequently converted to ROS and O2 by IrOx component. Thus, these enzymatic activities endow A-NiB@C-IrOx nanozymes with the ability of unceasing generation of ROS and O2 and depletion of GSH. In vitro and in vivo studies demonstrate a high therapeutic efficiency of A-NiB@C-IrOx nanozymes via apoptosis-ferroptosis combination therapy. Statement of significance: Apoptosis-ferroptosis hybrid therapy opens up new avenues for eradicating tumor cells. However, its actual therapeutic effect is still unsatisfied. Current efforts on this hybrid therapy focus on developing efficient self-cascade nanozymes to improve the efficiency of both ROS generation and GSH depletion. In this study, we constructed amorphous NiB alloy with a completed thin layer of IrOx shell (denoted as A-NiB@C-IrOx ) for apoptosis-ferroptosis combination therapy. As expected, A-NiB@C-IrOx can trigger efficient cascade catalytic reactions to continuously generate ROS and consume GSH, finally inducing augmented apoptosis-ferroptosis combination therapy. Graphical Abstract: Image, graphical abstract